Optimization Of Process Parameters For Cellulase And Xylanase Production Using Rice Husk - POONAM SANGWAN; VIKRAM MOR; RAJESH DHANKHAR; SEEMA SUKHANI (International Journal of Pharma and Bio Sciences, 2015)
The potential of Trichoderma atroviride for cellulase and xylanase production using Rice husk was carried out by Response Surface Methodology and Box-Behnken design. The experiment established the optimum conditions of incubation time (5.5 days), temperature (32.50C), pH (5.5), spore suspension (1.75ml) for solid state fermentation that led to the maximum production of cellulase and xylanase at a level of 90.43 IU/gds, 10.12 IU/gds. Good correlation was observed between the actual and predicted results indicated that the present model was applicable production of cellulase and xylanase.